2022
DOI: 10.1039/d2nj02949a
|View full text |Cite
|
Sign up to set email alerts
|

Arylation of aldehydes catalyzed by fluorinated NHC–Rh(i) complexes

Abstract: The synthesis and characterization of twelve Rh(I) complexes with fluorinated NHC ligands is described. Seven molecular structures of these complexes were unequivocally elucidated by single crystal X-ray diffraction techniques. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Br-e-TAP (5d)-catalyzed arylation of aqueous formaldehyde with arylboronic acids and aryl boronates [a] [a] Reaction conditions A: an aqueous formaldehyde solution (37 wt%, 1.25 mmol), 9 (0.50 mmol), Br-e-TAP (5d), and Cs2CO3 (1.0 mmol) were reacted in THF (0.5 mL) at 50 °C for 3 h. Reaction conditions B: an aqueous formaldehyde solution (37 wt%, 1.25 mmol), 7 (0.50 mmol), Br-e-TAP 5d and CsF (1.0 mmol) were reacted in THF (0. Overall, these results indicate that the MIC-coordinated cyclometalated palladium complexes (5), which were generated via oxidative addition between the 2-halophenyl group on the side chain of the MIC and zero-valent palladium, functioned as the catalytically active species (Scheme 3). NHC-coordinated allyl palladium complexes readily undergo reductive elimination under Suzuki-Miyaura coupling conditions to yield zero-valent palladium complexes.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Br-e-TAP (5d)-catalyzed arylation of aqueous formaldehyde with arylboronic acids and aryl boronates [a] [a] Reaction conditions A: an aqueous formaldehyde solution (37 wt%, 1.25 mmol), 9 (0.50 mmol), Br-e-TAP (5d), and Cs2CO3 (1.0 mmol) were reacted in THF (0.5 mL) at 50 °C for 3 h. Reaction conditions B: an aqueous formaldehyde solution (37 wt%, 1.25 mmol), 7 (0.50 mmol), Br-e-TAP 5d and CsF (1.0 mmol) were reacted in THF (0. Overall, these results indicate that the MIC-coordinated cyclometalated palladium complexes (5), which were generated via oxidative addition between the 2-halophenyl group on the side chain of the MIC and zero-valent palladium, functioned as the catalytically active species (Scheme 3). NHC-coordinated allyl palladium complexes readily undergo reductive elimination under Suzuki-Miyaura coupling conditions to yield zero-valent palladium complexes.…”
Section: Resultsmentioning
confidence: 85%
“…[3] Recently, transition-metal-catalyzed addition reactions involving carbonyl compounds using aryl boron compounds as nucleophiles have drawn attention for the synthesis of highly functionalized alcohols because of their superiority to the Grignard reaction in terms of functional group tolerance. [4][5][6][7][8][9] Strong σ-donating ligands, such as tertiary phosphines and NHCs, are effective for this type of addition reaction, and the use of NHCs with greater donating attributes in Rh- [5,6] and Pd-assisted [7,8] catalysis tends to reduce catalyst loading. However, their catalysts are limited to Arduengo-type NHCs, and the catalytic activity is expected to be improved using the more donor-oriented MICs.…”
Section: Introductionmentioning
confidence: 99%
“…25,28 Recently, we have reported that the catalytic activity of Rh( i ) complexes with fluorinated NHC ligands derived from imidazo[1,5- a ]pyridine is strongly related with the number of fluorine atoms present on their structures; the more fluorine atoms are attached to the NHC ligand, the more active the related complex becomes. 29 Also, fluorine atoms can tune some important properties of organic compounds such as acidity, conformation or lipophilicity. The latter are key properties for the design of pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…1). 29,37 Furthermore, we studied the supramolecular interactions of six selenourea compounds by Hirshfeld surface analysis and 2D dimensional fingerprint plots.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recently, transition-metal-catalyzed addition reactions involving carbonyl compounds using aryl boron compounds as nucleophiles have drawn attention for the synthesis of highly functionalized alcohols because of their superiority to the Grignard reaction in terms of functional group tolerance. [4][5][6][7][8][9] Strong σ-donating ligands, such as tertiary phosphines and NHCs, are effective for this type of addition reaction, and the use of NHCs with greater donating attributes in Rh- [5,6] and Pdassisted [7,8] catalysis tends to reduce catalyst loading. However, their catalysts are limited to Arduengo-type NHCs, and the catalytic activity is expected to be improved using the more donor-oriented MICs.…”
Section: Introductionmentioning
confidence: 99%